2018
DOI: 10.1016/j.bjm.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia determines transcriptional profile of microorganisms in anaerobic digestion

Abstract: Anaerobic digestion is important for the management of livestock manure with high ammonia level. Although ammonia effects on anaerobic digestion have been comprehensively studied, the molecular mechanism underlying ammonia inhibition still remains elusive. In this study, based on metatranscriptomic analysis, the transcriptional profile of microbial community in anaerobic digestion under low (1500 mg L−1) and high NH4+ (5000 mg L−1) concentrations, respectively, were revealed. The results showed that high NH4+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Some reduction is expected as a result of the consumption of nitrogen by microbial growth in the activated sludge layer, but is countered by the high level of NH 3 produced in the ABR as a component of biogas, leading to a flatter curve overall [7]. The smaller changes are consistent with the observation that the microorganisms involved in nitrogen removal are generally slow growing during anaerobic digestion [26].…”
Section: Reduction In Phosphate and Tknsupporting
confidence: 67%
“…Some reduction is expected as a result of the consumption of nitrogen by microbial growth in the activated sludge layer, but is countered by the high level of NH 3 produced in the ABR as a component of biogas, leading to a flatter curve overall [7]. The smaller changes are consistent with the observation that the microorganisms involved in nitrogen removal are generally slow growing during anaerobic digestion [26].…”
Section: Reduction In Phosphate and Tknsupporting
confidence: 67%
“…With the hydrolysis of starch, the structure of protein tended to reduce its compactness and some of them would dissolve in the aqueous phase. Generally, the protein in the free state is easier to be degraded to produce ammonia [37]. In this study the enzymatic hydrolysis was conducted in the reactors without hermetical and 14 amicrobic environment.…”
Section: Analysis Of the Chemical Components Of Hydrolysatementioning
confidence: 99%
“…Fontana et al performed a metagenomic study of one- and two-phase thermophilic AD of cheese wastewater; the results showed that the microbial community structures were significantly different between the two types of AD reactors and that increased microbial diversity was observed in the two-phase AD reactors [ 12 ]. Zhang et al found that a high concentration of ammonia nitrogen was beneficial for the accumulation of VFAs but can inhibit Acetyl-CoA and Methyl-CoM gene expression, thereby significantly inhibiting the methane metabolism pathway [ 13 ]. Hu et al analyzed the biodegradation pathway in an optimized activated carbon-containing AD reactor using Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis and found that the abundance of the pathways involved in the conversion of propionic acid into acetic acid was increased in the activated carbon-enhanced reactor and that the pathways involved in lipid and methane metabolism were also enhanced [ 14 ].…”
Section: Introductionmentioning
confidence: 99%